Analysis of alternatives for qualifying precarious settlements in environmentally fragile areas: application of grounded theory - Moscarelli, Fernanda da Cruz (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The reality of the Brazilian and Latin-American metropolitan areas, surrounded by precarious settlements, often located in environmentally fragile areas, have demanded from the State a set of qualification actions. However, these are only justifiable if they keep a sustainable character. This paper propose, through a case study, the adaptation of the grounded theory for the analysis of the connections between environmental data, thus supporting decision making in intervention programs. It was observed that several difficulties related to the analysis and processing of information were overcome, since the identification of the critical category, the systematic breakdown of information and its organization in matrixes allowed the identification of future consequences of the actions to be accomplished, stressing the systemic approach aimed by the researchers.